Qualidade de pão-de-forma sem glúten a base co-produtos de arroz e soja, com hidrocolóides e ou transglutaminase - Deus, Kátia Oliveira de (2015)
The search for baked goods without gluten good physical, chemical and microbiological, and acceptance have provided various surveys. In order to replace the gluten in breads consumer medium for celiac disease patients, various strategies have been employed such as the use of hydrocolloids and enzymes. The aim of this study was to evaluate the feasibility of a technological standpoint, nutritional, microbiological and acceptance of gluten-free bun obtained from different proportions soy by-products (okara) and rice (bran and grain flour broken), type and dose of hydrocolloids, and dose of transglutaminase enzyme, seeking alternatives to supply the growing market for products for coeliacs, as well as enhancement of agro-industrial subproutos rice and soybeans. All formulations had good sensory acceptance by the tasters, but with 65 g 100 g-1 rice flour, 10 g 100 g-1 rice bran and 25 g 100 g-1 okara flour presented the best physical quality, obtaining the greater desirability compared to commercial standard, and was accepted sensory, with average grade above 6 (like slightly). Use of hydrocolloids increased the specific volume of loaves of bread and improved textural characteristics. The form of gluten bread with 2 g 100g-1 of xanthan gum showed the highest specific volume (1.82 cm3 g-1). The transglutaminase of microbial origin increased by 9 %, the specific volume of gluten loaves with 10 U of transglutaminase per g of protein, 16 % lower hardness, indicating softness of bread, which showed 5 % more cohesive than those without transglutaminase. Regarding the commercial form of the selected bread specific volume was obtained 11 % higher and 110 % softer than bread trade marks. The gluten form of bread made with 65 g 100 g-1 of rice flour, 10 g 100 g-1 of rice bran and 25 g 100 g-1 okara flour with the addition of 2 g 100 g-1 xanthan gum and 10 U transglutaminase per g protein, showed the best results in texture with 16 % less hardness, 5 % more cohesiveness, 9 % more bulk, more elastic 2 % and 10 % decrease in chewiness. The loaf of bread obtained sensory acceptance indicating their potential for marketing of food with 45.83 g 100g-1 protein, rich in dietary fiber (10.17 g 100 g-1), and 1.61 g 100 g-1 in soluble fiber and 8.57 g 100 g-1 in insoluble fiber, providing a healthier alternative for consumers of celiac disease patients.